Visita de criança em Unidade de Terapia Intensiva em um Hospital Público: elaboração de protocolo - Taba, Sheila (2012)
Child visitation in Intensive Care Unit (ICU) is a conflicting situation in which the multidisciplinary team bears the responsibility of deciding upon allowing or not the child to visit a relative who is hospitalized. The reflections are individual, and the decisions are based on the professional's subjectivity. The growing demand ofvisitation ofchildren under the age established in hospital norms requires a more accurate reflection on the theme and the systematizing of a processo Thus, this study aims to create a 2-12-year-old child visitation protocol at Adult and Child Intensive Care Units in public hospitaIs. Considering the rights of the child, the patient, and the family as well as the dynamics of this hospital unit, child visitation to critical patients will be understood as a step forward in healthcare improvement, in agreement with healthcare policies of the Sistema Único de Saúde (SUS), the Brazilian public healthcare system within the HumanizaSus program guidelines. The child visitation to her hospitalized relative aims to align ethics with the needs emerging in modern society. In one year, 11 evaluations of child visitation at adult and child Intensive Care Units, for SUS paiients only, were performed. The requirements for visitation were spontaneous and the evaluation of permission or restriction included observation and intervlew by the researcher with the patient, the child, and the farnily, in addition to the team's judgment andinformation collected in the files. From the 17 children evaluated, 13 were allowed entrance and were followed in the visitation. Afterwards, inforrnation on their behavior and adverse reactions during the visit was collected with the relatives. The results showed that the visits occurred without incidents or problems. The entrance of the four children who were not allowed was denied by their families. The protocol was improved throughout the research and has proven adequate in helping on the decision by professionals involved